Use of the Site-Specific Retargeting Jump-In Platform Cell Line to Support Biologic Drug Discovery. (April 2015) - Butler, Robin; Hornigold, David; Huang, Ling; Huntington, Catherine; London, Tim; Dillon, Janette; Tigue, Natalie J.; Rossi, Alessandra; Naylor, Jacqueline; Wilkinson, Trevor
Biologics represent a fast-growing class of therapeutics in the pharmaceutical sector. Discovery of therapeutic antibodies and characterization of peptides can necessitate high expression of the target gene requiring the generation of clonal stably transfected cell lines. Traditional challenges of stable cell line transfection include gene silencing and cell-to-cell variability. Our inability to control these can present challenges in lead isolation. Recent progress in site-specific targeting of transgene to specific genomic loci has transformed the ability to generate stably transfected mammalian cell lines. In this article, we describe how the use of the Jump-In platform (Life Technologies, Carlsbad, CA) has been applied to drug discovery projects. It can easily and rapidly generate homogeneous high-expressing cell pools with a high degree of reproducibility. Their use in cell-based screening to identify specific binders, identify binding to relevant species variants, or detect functionally relevant therapeutic antibodies is central in driving drug discovery.